2016
DOI: 10.1186/s12934-016-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

The ACEII recombinant Trichoderma reesei QM9414 strains with enhanced xylanase production and its applications in production of xylitol from tree barks

Abstract: BackgroundACEII transcription factor plays a significant role in regulating the expression of cellulase and hemicellulase encoding genes. Apart from ACEII, transcription factors such as XYR1, CRE1, HAP2/3/5 complex and ACEI function in a coordinated pattern for regulating the gene expression of cellulases and hemicellulases. Studies have demonstrated that ACEII gene deletion results in decreased total cellulase and xylanase activities with reduced transcript levels of lignocellulolytic enzymes.ResultsIn this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…These results indicated that the expression of ace2 in T. orientalis largely improved the β-glucosidase activity and xylanase activity. In T. reesei, deletion of ace2 gene resulted in reduced expression levels of cellulases on Solka oc cellulose [18,19] and overexpression of ace2 gene exhibited signi cant increase in [20]. However, in contrast with the claim of Ace2 activating the cellulase production, most of the cellulase activities decreased after expressing ace2 in EU7-22.…”
Section: Enzyme Activity Of Transformants and Totalmentioning
confidence: 96%
See 1 more Smart Citation
“…These results indicated that the expression of ace2 in T. orientalis largely improved the β-glucosidase activity and xylanase activity. In T. reesei, deletion of ace2 gene resulted in reduced expression levels of cellulases on Solka oc cellulose [18,19] and overexpression of ace2 gene exhibited signi cant increase in [20]. However, in contrast with the claim of Ace2 activating the cellulase production, most of the cellulase activities decreased after expressing ace2 in EU7-22.…”
Section: Enzyme Activity Of Transformants and Totalmentioning
confidence: 96%
“…Some relevant studies were given by Xiong et al They have successfully transformed the Ace2 transcription factor encoding gene in T. reesei and gotten ve genetically engineered strains. Among which, the result displayed that only one has exhibited a signi cant increase in enzyme activity, but the other four showed lower total cellulase activities than the parental strain T. reesei QM9414 [20]. Also, Ace2 was not subject to carbon catabolite repression, because in the △cre1 strain no increased expression levels of ace2 gene were observed.…”
Section: Introductionmentioning
confidence: 97%
“…The role of Ace2 as a positive regulator of cellulase expression was further confirmed in another study where the overexpression of Ace2 in T. reesei led to a twofold increase in cellulase activity in the recombinant T/Ace2-2 strain when grown in a medium containing a mixture of hardwoods supplemented with glucose or xylose. [ 60 ].…”
Section: Transcriptional Regulators Involved In the Regulation Of Cel...mentioning
confidence: 99%
“…Perez-Gonzalez and coworkers (1996) Filamentous fungi are preferred expression systems because of the ease in handling fungal cultivation and strain improvement they have already undergone (Nevalainenm et al, 2005). Xylanases have been expressed in T. reesei, A. kawachii, and A. niger (Xiong et al, 2016;Qiu et al, 2016;Takahashi et al, 2013). P. pastoris has been explored for the expression of transgenic xylanase.…”
Section: Genetic Engineering Of Microorganisms For Maximization Of Xymentioning
confidence: 99%